Recovery of protease from heat-treated crude mango peel (Mangifera indica cv. Chokanan) feedstock by expanded bed adsorption - Amid, Mehrnoush; Abd. Manap, Mohd. Yazid (WFL Publisher, 2014)
The purification of serine protease from crude mango peel feedstock using heat-treated expanded bed adsorption was investigated. Streamline-DEAE adsorbent was used for the direct recovery of serine protease from thermal- and non-thermal treatment of crude feedstock. Chromatography is one of the most important separation techniques, which has been extensively used for the isolation and purification of proteins. Expanded bed adsorption (EBA) has been demonstrated as an efficient technology for separation and purification of proteins directly from unclarified feedstock. Expanded bed chromatography matrices are also available with various ligands and have been successfully applied in many capture chromatographies. In the study, the purification factor and yield of non-thermal treatment of feedstock were 5.8 and 75%, respectively. Heat-treated crude feedstock at 50°C resulted in 2 and 1.2 fold increases in purification factor and yield of serine protease, respectively, compared with that purified from non-heat-treated feedstock. Heating was found to be an important factor in reducing the level of contaminant proteins, therefore non-specific interaction between contaminant and adsorbent was decreased. Dynamic binding capacity and equilibrium adsorption isotherm were increased using heat treatment and enzyme activity assay indicated that the heat treatment had no negative effect on activity of serine protease.